Inhibition of Vibrio parahaemolyticus infection in whiteleg shrimp reared in a biofloc system with different volumes - Bako, Surandha; Widanarni, Widanarni; Ekasari, Julie; Yuhana, Munti (Jurnal Akuakultur Indonesia, 2024)
This study aimed to evaluate the inhibition of V. parahaemolyticus infection in the whiteleg shrimp (Penaeus vannamei) reared in different volumes of biofloc system. Post-larval shrimp with an average body weight of 0.28 ± 0.01 g were reared in 15 aquariums with working volume of 33.3 L and stocking density of 3 shrimp per liter. The shrimp were reared for 21 days in a biofloc system (C:N ratio of 10) with biofloc volume of 5, 10, and 15 mL/L, and challenged with V. parahaemolyticus at a density of 103 CFU/mL initially. The positive control treatment involved shrimp reared without biofloc and challenged, while the negative control treatment involved shrimp reared without biofloc and without challenged. The shrimp was fed with commercial feed while the protein content of 39-40% four times a day. The results showed that the presumptive Vibrio count (PVC) and the population of V. parahaemolyticus in the biofloc treatments were significantly lower than the positive control (p<0.05). Furthermore, the biofloc treatment with a volume of 15 mL/L demonstrated the best results compared to other treatments in decreasing PVC and V. parahaemolyticus population as evidenced by the immune response, survival rate, and growth performance of whiteleg shrimp. Keywords: biofloc, immune response, Penaeus vannamei, Vibrio parahaemolyticus ABSTRAK Penelitian ini bertujuan untuk mengevaluasi penghambatan infeksi V. parahaemolyticus pada udang vaname (Penaeus vannamei) yang dipelihara dalam sistem bioflok dengan volume yang berbeda. Post-larvae udang dengan bobot tubuh rata-rata 0,28 ± 0,01 g dipelihara dalam 15 akuarium dengan volume kerja 33.3 L dan padat tebar 3 udang per liter. Udang dipelihara selama 21 hari dalam sistem bioflok (rasio C:N 10) dengan volume bioflok 5, 10, dan 15 mL/L, dan diuji tantang dengan V. parahaemolyticus pada kepadatan awal 103 CFU/mL. Perlakuan kontrol positif melibatkan udang yang dipelihara tanpa bioflok dan diuji tantang, sementara perlakuan kontrol negatif melibatkan udang yang dipelihara tanpa bioflok dan tanpa diuji tantang. Udang diberi pakan komersial dengan kandungan protein 39-40% empat kali sehari. Hasilnya menunjukkan bahwa presumptive Vibrio count (PVC) dan populasi V. parahaemolyticus dalam perlakuan bioflok signifikan lebih rendah daripada kontrol positif (p<0,05). Selain itu, perlakuan bioflok dengan volume 15 mL/L menunjukkan hasil terbaik dibandingkan dengan perlakuan lain dalam menurunkan PVC dan populasi V. parahaemolyticus sebagaimana dibuktikan oleh respons imun, tingkat kelangsungan hidup, dan kinerja pertumbuhan udang vaname. Kata kunci: bioflok, Penaeus vanname, respons imun, Vibrio parahaemolyticus